Pengaruh Komunikasi Kerja Terhadap Produktivitas Kerja Pada PT. Pelabuhan Indonesia (Persero) Regional I - Masniati Murni Ritongan; Rara Ayu Jingga (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
One of the assets owned by the company is employee work productivity, in order to produce good productivity for the company. To increase employee productivity, a good communication is needed in the company. A leader provides direction for his employees to communicate well and create a sense of comfort at work. This research was conducted to determine the relationship between work communication on employee work productivity at PT. Pelabuhan Indonesia (Persero) Regional I . This study used a quantitative method with data obtained by distributing questionnaires to 31 respondents who were the sample. Based on the values ​​obtained, it states that the T test with a significant value of work communication 0.000 <0.05 means that work communication has a positive and significant effect on work productivity in the HR & General services division for employees, so that the hypothesis Ho is rejected and Ha is accepted, and the results of the coefficient test determination is 82% while the remaining 17% is influenced by other variables outside of this study. So the advice that can be given is to improve work communication so that employees have good work productivity and understand the goals desired and trusted by the company.